2012
DOI: 10.1186/1752-153x-6-123
|View full text |Cite
|
Sign up to set email alerts
|

Design of optimal solvent for extraction of bio–active ingredients from six varieties of Medicago sativa

Abstract: BackgroundExtensive research has been performed worldwide and important evidences were collected to show the immense potential of plants used in various traditional therapeutic systems. The aim of this work is to investigate the different extracting solvents in terms of the influence of their polarity on the extracting ability of bioactive molecules (phenolic compounds) from the M. sativa flowers.ResultsThe total phenolic content of samples was determined using the Folin Ciocalteu (FC) procedure and their anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 28 publications
1
32
0
2
Order By: Relevance
“…Antioxidant capacity of the extracts is largely dependent on the solvent polarity due to the different potential of compound polarity [9]. In this study, extracts from lower ethanol concentrations appeared higher DPPH (40%, v/v) and ABTS (30%, v/v) radical-scavenging capacities.…”
Section: Effects Of Different Ethanol Concentrationmentioning
confidence: 69%
See 2 more Smart Citations
“…Antioxidant capacity of the extracts is largely dependent on the solvent polarity due to the different potential of compound polarity [9]. In this study, extracts from lower ethanol concentrations appeared higher DPPH (40%, v/v) and ABTS (30%, v/v) radical-scavenging capacities.…”
Section: Effects Of Different Ethanol Concentrationmentioning
confidence: 69%
“…In several studies, different amounts of flavonoids have been found in alfalfa tissues, which indicated that it may be utilized as a potential natural antioxidant compound [9][10][11][12]. Alfalfa may be a promising resource for flavonoids in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenols are liable for antibiotic against microbial agents [24]. [25]. The resistance observed by B. subtillis in methanolic extracts is more than ethanolic extract, while in the case of gram-negative bacteria E. coli was not sensitive to any of the extracts.…”
Section: Analysis Of Gc-ms Profilementioning
confidence: 99%
“…It was shown that M. sativa flowers also display notable DPPH radical scavenging activity. [33] Flavonoids are predominantly located in aerial parts of the plants because synthesis of quercetin and other flavonoid derivatives is induced by the sunlight. [3] The role of flavonoids as radical scavengers [34] in the extracts of M. sativa aerial parts is confirmed in this work by the observed negative correlation (P < 0.05) between TF and RSA IC50.…”
Section: Radical Scavenging Activity Of the Extractsmentioning
confidence: 99%